Pertanggungjawaban Pidana bagi Pelaku Pencemaran Lingkungan Perspektif Fikih Jinayah - Umaya Miftha Ul Husna; Iwan Iwan (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This study aims to identify and analyze the strengths and weaknesses of the criminal liability system in environmental law and evaluate how Islamic jurisprudence can offer alternative or additional solutions to address environmental pollution problems. This study uses an empirical legal research method with qualitative procedures. The results of the study indicate that the act is considered to violate Islamic jurisprudence and environmental regulations in Indonesia, as shown in the findings. However, law enforcement still has obstacles related to evidence collection and time constraints that must be overcome in order to effectively pursue individuals or groups responsible for environmental damage. Therefore, to ensure environmental sustainability, it is important for the government to actively participate, for law enforcement to achieve effectiveness, and for business entities and the community to be aware of their obligations and be responsible for their behavior.